2011
DOI: 10.1007/s10439-011-0417-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Wall Engineering Via Femtosecond Laser Ablation: Scaffolds with Self-Containing Smooth Muscle Cell Populations

Abstract: For tissue-engineered vascular grafts to reach their full potential, three-dimensional (3D) cellular micro-integration will be necessary. In this study, we utilize femtosecond laser ablation to produce microchannels inside electrospun polycaprolactone (PCL) scaffolds. These microchannels potentially provide spatially controlled cell distributions approaching those observed in vivo. The ability of such laser-ablated microchannels to direct cell seeding was evaluated. The dimensions chosen were 100 μm wide, 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Together, these results show that GBM migration in the presence of astrocytes is a complex process with both pro-and inhibitory cues, and additional mechanisms beyond the scope of this study likely also contribute. For example, a previous study showed a decrease in glioma migration when astrocyteglioma gap junctions were inhibited, 13 suggesting that interactions between the two cell types positively influence migration of glioma cells, similar to our experimental observations. In both the GFAP and migration studies, it should be noted that the chemical fixation methods employed and the use of proteolytic agents for cell removal may influence results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Together, these results show that GBM migration in the presence of astrocytes is a complex process with both pro-and inhibitory cues, and additional mechanisms beyond the scope of this study likely also contribute. For example, a previous study showed a decrease in glioma migration when astrocyteglioma gap junctions were inhibited, 13 suggesting that interactions between the two cell types positively influence migration of glioma cells, similar to our experimental observations. In both the GFAP and migration studies, it should be noted that the chemical fixation methods employed and the use of proteolytic agents for cell removal may influence results.…”
Section: Discussionsupporting
confidence: 91%
“…8,10 Previous work investigating GBMastrocyte interactions has demonstrated that astrocytes upregulate expression of GFAP and matrix metalloproteinase-2 (MMP-2) in the presence of GBM cells 11,12 and has also shown that astrocytes play a supportive role in GBM migration. 13 Thus, in these investigations, we evaluated the relationship between these two well-established characteristics of normal astrocytes and GBM cells, respectively: GFAP expression and cell migration. In addition, previously reported experiments primarily relied on two dimensional (2D) tissue culture polystyrene substrates that fail to capture unique topographical features of the tumor microenvironment, particularly the blood vessel and white matter tracts along which GBMs migrate.…”
Section: Introductionmentioning
confidence: 99%
“…After cooling to room temperature, the uniformly mixed solution was electrospun according to procedures used previously. [18, 19] The large diameter PCL fibers were fabricated by using dichloromethane (DCM) as the solvent. The typical sample thickness (approximately 100 μm) for sensing applications was held constant by fixing the deposition time at 400 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, many synthetic material systems lack a porous bulk matrix surrounding the microchannels, which significantly limits utility in engineering tissues around the microchannels. Efforts have been reported to build porous micropatterned synthetic material systems, however the pores were small in diameter and cell infiltration into the bulk space was not demonstrated 9, 13…”
Section: Introductionmentioning
confidence: 99%